Ethnic tourism: the problem of conceptual terminology and methodical approaches to social-geographic studies - Yaroslav Dzhaman (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
The article deals with the analysis of foreign and national researchers’ approaches to definition of the concept of ethnic tourism. The majority of existing studies devoted to ethnic tourism inAmericaandEuropeconcentrate on describing it as trips to exotic and often isolated ethnic groups (Smith V., McIntosh R., Goeldner C., Van den Berghe P., Harron S., Weiler B.). Some scientists regard that ethnic tourism includes trips to forefathers’ homelands with the purpose of learning the own ethnic belonging – nostalgic tourism (King B.). Along with the term of ethnic tourism, the concepts of aboriginal tourism (Getz D., Jamieson W.) and native tourism (Butler R., Hinch T.) are widely used, though the same phenomenon is meant. Russian researchers use the concepts of ethnic tourism, ethnographic tourism and nostalgic tourism.